2021
DOI: 10.3389/fnut.2021.726108
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Displayed Amuc_1100 From Akkermansia muciniphila on Lactococcus lactis ZHY1 Improves Hepatic Steatosis and Intestinal Health in High-Fat-Fed Zebrafish

Abstract: Fatty liver and intestinal barrier damage were widespread in most farmed fish, which severely restrict the development of aquaculture. Therefore, there was an urgent need to develop green feed additives to maintain host liver and intestinal health. In this study, a probiotic pili-like protein, Amuc_1100 (AM protein), was anchored to the surface of Lactococcus lactis ZHY1, and the effects of the recombinant bacteria AM-ZHY1 on liver fat accumulation and intestinal health were evaluated. Zebrafish were fed a bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Probiotics including Adlercreutzia , Leuconostoc , Lactococcus and Oscillospira were significantly reduced in the fructose intake group, while some bacteria associated with induced inflammation and diseases ( Allobaculum and Holdemania , Figure 4 D) were observed to be enriched in fructose intake group. Adlercreutzia [ 27 ], Leuconoxtoc [ 31 ], Lactococcus [ 32 ] and Oscillospira [ 42 ] were proven as probiotic or had a positive correlation with human/animal health. It is hinted that even though both sucrose and fructose changed gut bacteria in experimental colitis rats, fructose levels tended to change for the worse situation.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics including Adlercreutzia , Leuconostoc , Lactococcus and Oscillospira were significantly reduced in the fructose intake group, while some bacteria associated with induced inflammation and diseases ( Allobaculum and Holdemania , Figure 4 D) were observed to be enriched in fructose intake group. Adlercreutzia [ 27 ], Leuconoxtoc [ 31 ], Lactococcus [ 32 ] and Oscillospira [ 42 ] were proven as probiotic or had a positive correlation with human/animal health. It is hinted that even though both sucrose and fructose changed gut bacteria in experimental colitis rats, fructose levels tended to change for the worse situation.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal TJ proteins, including occludin, claudin, and ZO-1 play an important role in maintaining gut permeability and barrier function ( 48 ). Previous studies reported that as the TJ expression levels decreased induced by HFD, the gut permeability increased, which lead to increased level of serum endotoxemia and impaired immune response ( 42 , 48 ). We investigated whether probiotic P. pentosaceus PR-1 could improve gut barrier function in HFD-fed zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found zebrafish serve as a useful animal model of human HFD-induced obesity for research into the alterations of gut microbiota community and inflammation driven by HFD due to its similarity of organs to humans, the availability of a complete genome sequence, and its highly conserved physiological pathways (2,(38)(39)(40)(41)(42)(43). Although zebrafish is dominated by Proteobacteria, mice and human are dominated by Firmicutes and Bacteroidetes, the response to microbiota colonization are similar (44).…”
mentioning
confidence: 99%
“…Cell line experiments have also shown that activation of TLR2 can increase the expression of tight junction proteins 232 , which may be the mechanism by which A. muciniphila improves barrier function (Fig. 2) 233 . In human trials, A. muciniphila Muc can improve barrier function, as shown by reduced plasma LPS levels, however this effect was only significant when pasteurised cells and not live cells were ingested 163 .…”
Section: Modulation Of Innate Immune Functionmentioning
confidence: 96%